A note on nonfragmentability of Banach spaces. (1st July 2001) - Mirmostafaee, S. Alireza Kamel
Abstract : We use Kenderov-Moors characterization of fragmentability to show that if a compact Hausdorff spaceX with the tree-completeness property contains a disjoint sequences of clopen sets, then (C ( X ), weak) is not fragmented by any metric which is stronger than weak topology. In particular, C ( X ) does not admit any equivalent locally uniformly convex renorming.